Insect egg deposition renders plant defence against hatching larvae more effective in a salicylic acid‐dependent manner. (19th November 2018) - Lortzing, Vivien; Oberländer, Jana; Lortzing, Tobias; Tohge, Takayuki; Steppuhn, Anke; Kunze, Reinhard; Hilker, Monika
Abstract: Plants can improve their antiherbivore defence by taking insect egg deposition as cue of impending feeding damage. Previous studies showed that Pieris brassicae larvae feeding upon egg‐deposited Brassicaceae perform worse and gain less weight than larvae on egg‐free plants. We investigated how P. brassicae oviposition on Arabidopsis thaliana affects the plant's molecular and chemical responses to larvae. A transcriptome comparison of feeding‐damaged leaves without and with prior oviposition revealed about 200 differently expressed genes, including enhanced expression of PR5, which is involved in salicylic acid (SA)‐signalling. SA levels were induced by larval feeding to a slightly greater extent in egg‐deposited than egg‐free plants. The adverse effect of egg‐deposited wild‐type (WT) plants on larval weight was absent in an egg‐deposited PR5‐deficient mutant or other mutants impaired in SA‐mediated signalling, that is, sid2/ics1, ald1, and pad4 . In contrast, the adverse effect of egg‐deposited WT plants on larvae was retained in egg‐deposited npr1 and wrky70 mutants impaired further downstream in SA‐signalling. Oviposition induced accumulation of flavonols in WT plants with and without feeding damage, but not in the PR5‐deficient mutant. We demonstrated that egg‐mediated improvement of A. thaliana 's antiherbivore defence involves SA‐signalling in an NPR1‐independent manner and is associated with accumulation of flavonols. Abstract : The response of Arabidopsis thaliana plants to insect eggs reinforces their feeding‐induced defence against hatching larvae. This improved defence relies on salicylic acid signalling, is independent of NPR1, requires PR5, and involves enhanced phenylpropanoid levels that may impair the larvae.